2012
DOI: 10.4104/pcrj.2012.00013
|View full text |Cite
|
Sign up to set email alerts
|

A centralised respiratory diagnostic service for primary care: a 4-year audit

Abstract: Background: The literature shows that delayed or erroneous diagnosis of respiratory conditions may be common in primary care due to underuse of spirometry or poor spirometric technique. The Community Respiratory Assessment Unit (CRAU) was established to optimise diagnosis and treatment of respiratory disease by providing focused history-taking, quality-assured spirometry, and evidence-based guideline-derived management advice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
48
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 24 publications
0
48
0
Order By: Relevance
“…The provisional diagnoses were compared with the final diagnosis after spirometry and respiratory specialist nurse review. Details of previous analyses from the CRAU database have been published elsewhere [6,7].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The provisional diagnoses were compared with the final diagnosis after spirometry and respiratory specialist nurse review. Details of previous analyses from the CRAU database have been published elsewhere [6,7].…”
Section: Methodsmentioning
confidence: 99%
“…A Community Respiratory Assessment Unit (CRAU) was established in 2004 in West London to provide diagnostic support to primary care physicians working within the Hammersmith and Fulham area [6]. An audit of the first four years of the programme has been published [7] and patients were referred from over 20 different general practices. The main driver for referral was likely to be the QOF process and it is not possible to determine how representative those referred to CRAU are of others attending those practices.…”
Section: Introductionmentioning
confidence: 99%
“…In specialist care, the most used methods for asthma diagnosing are spirometry and bronchial challenge. In Western Europe, spirometry is increasingly performed in PC settings, but the quality is questionable (30,31). In a recent study, 22% of spirometric tests carried out in PC setting showed no ERS/ATS guideline adherence, despite intensive training (32).…”
Section: Asthmamentioning
confidence: 99%
“…The cost is much lower than that of office spirometry. Nevertheless, there is a case for improving access to quality spirometry accessible by or delivered by GP, as accurate assessment leads to better clinical decision making and more appropriate prescribing (31).…”
Section: Asthmamentioning
confidence: 99%
“…Hence the early diagnosis of asthma and achieving acceptable asthma supervision at the right time remains evasive despite the existing methods. There are two methods to diagnose asthma; firstly, through clinical investigation carried out by the specialized physician [5]; secondly, by applying diagnostic equipment such as Spirometer and peak flow meter [5][6][7]. However, the first method could be inaccurate sometimes due to manual and involvement of human.…”
Section: Introductionmentioning
confidence: 99%